The Role of Exosomes in Diseases Related to Infertility - Jiayu, Huang; Hanke, Zhang; Ying, Gao (Current Stem Cell Research & Therapy, 2019)
Exosomes, small extracellular vesicles with diameters of 40-100nm, are generated through the fusion of multivessel with plasma membrane and secreted by a variety of living cells. Exosomes contain lipid bilayer membrane and releasable functionally active proteins, mRNA and microRNAs (miRNAs). This article reviews the latest progress of researches on exosomes in diseases that lead to infertility.
Keywords: reproductive medicine